Effect of cardiac rehabilitation on ventricular repolarization in patients with type 2 diabetes and coronary heart disease: Non-invasive quantification via transmural dispersion of repolarization - Tokatlı, Alptu?; Yi?iner, Ömer; Kılıçaslan, Fethi; Uzun, Mehmet Ali (Mosby-Elsevier, 2015)
We read the article entitled ‘Impacts of cardiac rehabilitation on ventricular repolarization indexes and ventricular arrhythmias in patients affected by coronary artery disease and type 2 diabetes’ by Boukhris M et al1 published in ‘Heart & Lung: The Journal of Acute and Critical Care’ with great interest. In this well designed research, they investigated the impact of cardiac rehabilitation program in patients with coronary artery disease and type 2 diabetes mellitus, on ventricular repolarization indexes and ventricular arrhythmias. In conclusion, they reported that after cardiac rehabilitation program, there were significant decreases in ventricular repolarization indices, namely QTc, QTc dispersion and JTc except for JTc dispersion. The frequency of ventricular arrhythmias according to Lown grading system significantly decreased in diabetics and non-diabetics however they stated that higher benefit was observed in patients with diabetes.
WOS: 000361017100018
PubMed ID: 26066368
Keywords: Cardiac Rehabilitation; Ventricular Repolarization; Non-invasive; Repolarization